Mechanical determinants of chromatin topology and gene expression. Issue 1 (31st December 2022) - Jha, Rajiv Kumar; Levens, David; Kouzine, Fedor
ABSTRACT: The compaction of linear DNA into micrometer-sized nuclear boundaries involves the establishment of specific three-dimensional (3D) DNA structures complexed with histone proteins that form chromatin. The resulting structures modulate essential nuclear processes such as transcription, replication, and repair to facilitate or impede their multi-step progression and these contribute to dynamic modification of the 3D-genome organization. It is generally accepted that protein–protein and protein–DNA interactions form the basis of 3D-genome organization. However, the constant generation of mechanical forces, torques, and other stresses produced by various proteins translocating along DNA could be playing a larger role in genome organization than currently appreciated. Clearly, a thorough understanding of the mechanical determinants imposed by DNA transactions on the 3D organization of the genome is required. We provide here an overview of our current knowledge and highlight the importance of DNA and chromatin mechanics in gene expression.